Successful Mechanical Thrombectomy of Middle Cerebral Artery Occlusion 14 Hours after Stroke Onset - Robin Bhattarai,; Karki, Karuna Tamrakar; Thapa, Dinesh Kumar; Yadav, Navin Kumar (Eastern Green Neurosurgery, 2021)
A 45-year-old patient with no significant past medical history presented to out-patient department with aphasia and right hand weakness with a National Institutes of Health Stroke Scale (NIHSS) of 10 and occlusion of the left middle cerebral artery (MCA) in the M1 segment. Last known normal time was 14hrs (wake up stroke). Immediate endovascular thrombectomy was performed 14 hours after symptom onset with complete recanalization and complete clinical recovery. Although mechanical thrombectomy is generally considered an effective alternative strategy up to 8 hours after stroke onset, selected patients with a large diffusion/perfusion mismatch and small infarct cores may benefit from an expanded therapeutic window.